Comparative Efficacy of Different Fungicides under Open and Protected Conditions Against Pea Powdery Mildew (Erysiphe pisi) in Cold Desert Zone of Himachal Pradesh - Jarial, R. S.; Jarial, Kumud; Gupta, Dharmesh; Sharma, C. L. (International Journal of Bio-resource and Stress Management, 2023)
Pea is the principal off season vegetable crop of dry temperate zone of Himachal Pradesh. The crop becomes highly susceptible to powdery mildew (Erysiphe pisi) due to highly fluctuating climate and meager humidity during the cropping season in the valley, resulting in huge losses. Experiments were conducted during 2010 and 2011 cropping seasons as randomized block design at research farm of Dr.Y. S Parmar University Regional Horticultural Research Sub Station, Tabo, Spiti, Himachal Pradesh both under natural epiphytotic and protected conditions. Plants of variety Azad P1 were raised in thirty five plots of size 2×2 m2. The seed was sown by broadcast method in all the plots. In all, six fungicides viz., Kitazin, Dimethomorph, Difenoconazole, Hexaconazole, Propiconazole and Carbendazim sprayed at 15 days interval starting from the first appearance of the disease symptoms were evaluated against the disease. It was found that the plots sprayed with hexaconazole exhibited minimum disease severity (35.50 and 16.50%, respectively) and maximum disease control (63.95 and 81.03%, respectively) pooled for two years both under natural and protected conditions. As far as pod yield was concerned, it was found to be inversely proportional to disease levels, being maximum in the plots with minimum disease severity and vice versa under both conditions in 2010 and 2011 crop seasons. The apparent infection rates pooled for two years varied from 0.04 to 0.12 unit-1 day-1 in plots sprayed with different fungicides which was quite low in comparison to untreated control plots exhibiting apparent infection rates of 0.38 and 0.30 unit-1 day-1 under natural and protected conditions, respectively.